Pushing the envelope through the Global Financing Facility: potential impact of mobilising additional support to scale-up life-saving interventions for women, children and adolescents in 50 high-burden countries. Issue 5 (2nd October 2018) - Chou, Victoria B; Bubb-Humfryes, Oliver; Sanders, Rachel; Walker, Neff; Stover, John; Cochrane, Tom; Stegmuller, Angela; Magalona, Sophia; Von Drehle, Christian; Walker, Damian G; Bonilla-Chacin, Maria Eugenia; Boer, Kimberly Rachel
Abstract : Introduction: The Global Financing Facility (GFF) was launched to accelerate progress towards the Sustainable Development Goals (SDGs) through scaled and sustainable financing for Reproductive, Maternal, Newborn, Child and Adolescent Health and Nutrition (RMNCAH-N) outcomes. Our objective was to estimate the potential impact of increased resources available to improve RMNCAH-N outcomes, from expanding and scaling up GFF support in 50 high-burden countries. Methods: The potential impact of GFF was estimated for the period 2017–2030. First, two scenarios were constructed to reflect conservative and ambitious assumptions around resources that could be mobilised by the GFF model, based on GFF Trust Fund resources of US$2.6  billion. Next, GFF impact was estimated by scaling up coverage of prioritised RMNCAH-N interventions under these resource scenarios. Resource availability was projected using an Excel-based model and health impacts and costs were estimated using the Lives Saved Tool (V.5.69 b9). Results: We estimate that the GFF partnership could collectively mobilise US$50–75  billion of additional funds for expanding delivery of life-saving health and nutrition interventions to reach coverage of at least 70% for most interventions by 2030. This could avert 34.7  million deaths—including preventable deaths of mothers, newborns, children and stillbirths—compared with flatlined coverage, or 12.4  million deaths compared with continuation of historic trends. Under-five and neonatal mortality rates are estimated to decrease by 35% and 34%, respectively, and stillbirths by 33%. Conclusion: The GFF partnership through country- contextualised prioritisation and innovative financing could go a long way in increasing spending on RMNCAH-N and closing the existing resource gap. Although not all countries will reach the SDGs by relying on gains from the GFF platform alone, the GFF provides countries with an opportunity to significantly improve RMNCAH-N outcomes through achievable, well-directed changes in resource allocation.